13-8x=183-43x

Simple and best practice solution for 13-8x=183-43x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-8x=183-43x equation:


Simplifying
13 + -8x = 183 + -43x

Solving
13 + -8x = 183 + -43x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43x' to each side of the equation.
13 + -8x + 43x = 183 + -43x + 43x

Combine like terms: -8x + 43x = 35x
13 + 35x = 183 + -43x + 43x

Combine like terms: -43x + 43x = 0
13 + 35x = 183 + 0
13 + 35x = 183

Add '-13' to each side of the equation.
13 + -13 + 35x = 183 + -13

Combine like terms: 13 + -13 = 0
0 + 35x = 183 + -13
35x = 183 + -13

Combine like terms: 183 + -13 = 170
35x = 170

Divide each side by '35'.
x = 4.857142857

Simplifying
x = 4.857142857

See similar equations:

| 36/n=9/11 | | 4-2/5x=0 | | 3/4x-2=4 | | 3x=8/2 | | (3x-4)*(5x+3)=1 | | 3x*3x=0 | | 4E+6= | | 7/2x+1-8x/2x-1=-4 | | (a-2)*(2*b+3)=26 | | 8x^3=64x^2 | | a(2.25a)=1614 | | x(2.25)=1614 | | 20x^4-40x^3= | | 16=x^2-10x+20 | | x/4+2x/3-5=x/3-3x/2+1/2 | | x/12-1/x=3/4x | | 5*0-7y=-35 | | (2-x^2)/(6x-x^3) | | 7x-9+4x=3x-3+12+9x | | -10*0+9y=-90 | | -8*0-2y=16 | | 8*0+2y=16 | | 3.2x+8.3=1.3x+19.7 | | -6=t/10-3 | | x(x-5)=(x+1)(3x+2) | | 7a+11=5a-9 | | s/6+90=-6 | | y=65x+30 | | 6=2a+20 | | 16-5x=2x-5 | | -18=-25.875x-18y | | x*2+16x-1161=0 |

Equations solver categories